Tom Randolph launches the virtual Livestock and Fish review and planning meeting - Randolph, Thomas F. (International Livestock Research Institute, 2015)
Tom Randolph to the CGIAR Research Program on Livestock and Fish review and planning meeting, 23-26 March 2015